2022
DOI: 10.3390/ph15091056
|View full text |Cite
|
Sign up to set email alerts
|

Gypenoside XLIX Ameliorate High-Fat Diet-Induced Atherosclerosis via Regulating Intestinal Microbiota, Alleviating Inflammatory Response and Restraining Oxidative Stress in ApoE−/− Mice

Abstract: A high-fat choline diet (HFCD)-induced atherosclerosis model in ApoE−/− mice was established to explore the anti-atherosclerotic effects of gypenoside XLIX (GPE). It was found that HFCD-induced atherosclerotic index such as dyslipidemia, atherosclerotic plaque, inflammation, and gut microbiota dysfunction could be reduced by GPE treatment. GPE treatment could decrease Verrucomicrobia, Proteobacteria, and Actinobacteria abundance, and increase Firmicutes and Bacteroidetes population. Moreover, the Firmicutes/Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Considering sex, 9 studies used males, 10 used females, only 2 included males and females and 5 did not report the sex of the mice. Considering the type of intervention, 17 studies tested berries, polyphenols or berberine [ 22 , 23 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and 9 used probiotics [ 11 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The intervention duration varied from 4 to 16 weeks of treatment, and all the studies used HFD to induce plaque.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering sex, 9 studies used males, 10 used females, only 2 included males and females and 5 did not report the sex of the mice. Considering the type of intervention, 17 studies tested berries, polyphenols or berberine [ 22 , 23 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and 9 used probiotics [ 11 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The intervention duration varied from 4 to 16 weeks of treatment, and all the studies used HFD to induce plaque.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the microbiome, only 10 studies reported F/B ratios. For atherosclerosis quantification, all of the included studies, except for one [ 37 ], reported aortic plaque size, which was reported for the aortic root (7 studies) [ 32 , 33 , 36 , 40 , 47 , 48 , 49 ], the arch (4 studies) [ 34 , 35 , 42 , 46 ], the aortic sinus (11 studies) [ 11 , 28 , 29 , 30 , 31 , 38 , 40 , 41 , 43 , 44 , 45 ] and in the whole aorta (7 studies) [ 22 , 23 , 27 , 28 , 35 , 39 , 46 ]. The study by Yang et al [ 37 ] reported a reduction in plaque in the aortic sinus by the intervention, but no quantification was provided.…”
Section: Resultsmentioning
confidence: 99%
“…Gynostemma pentaphyllum (Thunb.) Makino is an ancient Chinese herbal medicine and tea [ 87 ], and is known for its effects in reducing blood pressure, hypolipidemia, hypoglycemia and anti-aging [ 17 ]. Gypenoside has been identified as the most important functional component of Gynostemma pentaphyllum .…”
Section: Gypenosidesmentioning
confidence: 99%
“…There are more than 160 types of gypenoside that have been classified into 12 classes, such as gypenoside III, IV, VII, XII, I, Gyp-A-AH and XLIX, etc. [ 17 , 87 ]. Gypenosides possess a number of bioactivities including anti-atherogenesis, anti-inflammation, anti-cancer, neuroprotection, hepatoprotection and adjusting lipidemia [ 88 , 89 ].…”
Section: Gypenosidesmentioning
confidence: 99%
See 1 more Smart Citation